Public income transfers and wealth accumulation at the bottom: Within and between country differences in Canada and the United States. (30th July 2020) - Rothwell, David W.; Giordono, Leanne S.; Robson, Jennifer
Abstract: Both Canada and the United States are considered liberal welfare states, yet exhibit notable differences in income poverty attributed to social policy. While a more generous welfare system lifts many above income poverty, models of household financial behaviour suggest that more income from the state should displace private savings via a substitution effect. Using nationally representative wealth surveys from Canada and the US from 1998/1999 to 2016 we extend knowledge on the relationship between the welfare state and private wealth accumulation. Specifically, we study household asset poverty defined as financial asset levels that fall below three‐month adjusted income poverty threshold. Asset poverty rates varied over time in the two countries and were higher in the less generous US welfare state. Further, income transfer share was positively related to asset poverty in Canada but not in the US. Counterfactual estimates offered evidence of the substitution effect in Canada, where higher levels of transfers may crowd out private asset accumulation. Results invite further consideration of the concept of asset poverty and its relationship to welfare state characteristics.